2022
DOI: 10.1155/2022/7692086
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Fluctuations on Stock Markets: Empirical Evidence from South Asia

Abstract: The proportionate use of energy represents economic activity as well as environmental degradation. This study intends to examine the volatility spillover of environmental fluctuations (energy prices) to the stock markets of south Asian countries (i.e., Bangladesh, India, and Pakistan). In this regard, the data have been gathered from the Thomson Reuters DataStream from 2013 to 2021. This study has applied the Granger causality test and ARCH-GARCH (1, 1). It concludes that the bidirectional causality exists bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Environmental sustainability comprises making responsible decisions and taking action to protect the natural world, with a focus on human life-support [ 46 ]. Environmental sustainability has various compelling arguments.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Environmental sustainability comprises making responsible decisions and taking action to protect the natural world, with a focus on human life-support [ 46 ]. Environmental sustainability has various compelling arguments.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Further, efficient use of online shopping, e-commencing, teleconferences, and teleworking have made it possible to save time, money, and resources ( Sui and Rejeski, 2002 ; Mustafa et al, 2021 , 2022d , e ). The migration of the economy from carnal to information capitals helps improve environmental feature and reduce energy consumption, a sign of a weightless economy that demands less capital for operation ( Ozcan and Apergis, 2018 ; Huang et al, 2022 ; Khan et al, 2022 , 2021 ; Zahid et al, 2022a , b ). The said transformation has reduced the reliance of economies on physical resources for their growth process, reducing pollution emissions.…”
Section: Introductionmentioning
confidence: 99%
“…As with ANN, hybrid ANFIS may also detect nonlinear relationships between inputs and outputs. Several studies, such as those in [45][46][47][48][49], have shown that ANFIS has a higher prediction e ciency than individual ANNs or FL. As a sort of arti cial neural network, the ANFIS system relies on the Takagi-Sugeno fuzzy inference system, which combines the advantages of ANN and fuzzy logic in one framework.…”
Section: Input Gate Layermentioning
confidence: 99%